Biomarkers of necrotising soft tissue infections: aspects of the innate immune response and effects of hyperbaric oxygenation—the protocol of the prospective cohort BIONEC study. Issue 5 (11th May 2015) - Hansen, Marco Bo; Simonsen, Ulf; Garred, Peter; Hyldegaard, Ole
Abstract : Introduction: The mortality and amputation rates are still high in patients with necrotising soft tissue infections (NSTIs). It would be ideal to have a set of biomarkers that enables the clinician to identify high-risk patients with NSTI on admission. The objectives of this study are to evaluate inflammatory and vasoactive biomarkers as prognostic markers of severity and mortality in patients with NSTI and to investigate whether hyperbaric oxygen treatment (HBOT) is able to modulate these biomarkers. The overall hypothesis is that plasma biomarkers can be used as prognostic markers of severity and mortality in patients with NSTI and that HBOT reduces the inflammatory response. Methods and analysis: This is a prospective, observational study being conducted in a tertiary referral centre. Biomarkers will be measured in 114 patients who have been operatively diagnosed with NSTI. On admission, baseline blood values will be obtained. Following surgery and HBOT, daily blood samples for measuring regular inflammatory and vasoactive biomarkers (pentraxin-3, interleukin-6 and nitrite) will be acquired. Samples will be analysed using validated ELISA assays, chemiluminescence and Griess reaction. Clinical data will be obtained during admission in the intensive care unit for a maximum of 7 days. The primary analysis will focus on pentraxin-3, interleukin-6 and nitrite as early markers of disease severity in patients with NSTI. Ethics and dissemination: The study has been approved by the Regional Scientific Ethical Committee of Copenhagen (H-2–2014–071) and the Danish Data Protection Agency (J. no. 30–0900 and J. no. 30–1282). Results will be presented at national and international conferences and published in peer-reviewed scientific journals. Trial registration: NCT02180906.